Evaluating hydrologic effects of spatial and temporal patterns of forest canopy change using numerical modelling. Issue 2 (29th July 2015) - Du, Enhao; Link, Timothy E.; Wei, Liang; Marshall, John D.
Abstract: Although hydrologic responses to land cover changes are often studied using a paired watershed approach, it is not feasible to assess the hydrological effects of many different patterns of land cover alteration by empirical studies alone. An alternative is to use well validated, spatially explicit, physically based numerical models to estimate watershed storage and flux dynamics. The objectives of this study were to assess the sensitivity of watershed flow regimes to several spatial and temporal patterns of forest harvest and recovery in a snow‐dominated mountain watershed. The Distributed Hydrology Soil‐Vegetation Model (DHSVM) was parameterized using 1998–2007 climate data for the 28‐km 2 Mica Creek Experimental Watershed (MCEW), a headwater catchment in the inland Pacific Northwest. The modelling experiment indicated that clear‐cutting the entire watershed would increase runoff volume by 79% and 5 th percentile flows by 68%. Hydrologic recovery resulting from forest regeneration after clear‐cut harvesting is expected to take up to 25 years to return to baseline conditions, and 50 years to fully recover to preharvest conditions. A more realistic harvesting scenario where the watershed was gradually harvested in a series of clear‐cut blocks allowing for subsequent regeneration to occur was also assessed. This approach reduced the magnitude of hydrologic alteration. Analysis of several other scenarios, defined by aspect, elevation, and distance to the stream network, revealed that flow regime was more sensitive to the amount of alteration rather than pattern and landscape position of disturbance. Copyright © 2015 John Wiley & Sons, Ltd.